Blowing the whistle on corruption: the Enron story - Lovell, Alan (Henry Stewart Talks, 2018)
This case study looks at why whistleblowers reveal damaging information about companies they work for, even though it will reduce the value of the company and will quite likely lead to hostility from colleagues and loss of income to the whistleblower personally.